2010
DOI: 10.1051/0004-6361/200913894
|View full text |Cite
|
Sign up to set email alerts
|

Comparing six evolutionary population synthesis models by performing spectral synthesis for galaxies

Abstract: Aims. We compare six popularly used evolutionary population synthesis (EPS) models by fitting the full optical spectra of six representative types of galaxies (star-forming and composite galaxies, Seyfert 2s, LINERs, E+A, and early-type galaxies) taken from the Sloan Digital Sky Survey (SDSS). We explore the dependence of stellar population synthesis results on the main ingredients of the EPS models and study whether there is an age sequence among these types of galaxies. Methods. We use the simple stellar pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 107 publications
0
28
1
Order By: Relevance
“…It is also fundamental to choose an adequate number of elements for such library in order to have nondegenerate solutions (Schmidt et al 1991;Cid Fernandes et al 2005;Dametto et al 2014). Chen et al (2010) presented a study in the optical region showing that different models may result in quite different SFHs for the same observed spectrum. Studying six different types of galaxies (star-forming galaxies, composite galaxies, Seyfert 2s, LINERs, E+A, and ETGs) using six different EPS models, they found that the differences found are significant, but the dominant populations are unaltered.…”
Section: S T E L L a R P O P U L At I O N S Y N T H E S I Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is also fundamental to choose an adequate number of elements for such library in order to have nondegenerate solutions (Schmidt et al 1991;Cid Fernandes et al 2005;Dametto et al 2014). Chen et al (2010) presented a study in the optical region showing that different models may result in quite different SFHs for the same observed spectrum. Studying six different types of galaxies (star-forming galaxies, composite galaxies, Seyfert 2s, LINERs, E+A, and ETGs) using six different EPS models, they found that the differences found are significant, but the dominant populations are unaltered.…”
Section: S T E L L a R P O P U L At I O N S Y N T H E S I Smentioning
confidence: 99%
“…A major issue when characterizing the stellar population of a galaxy is attributed to the dependence of results in the model set used when fitting the underlying stellar features (Chen et al 2010). This happens because of all the uncertainties related to the construction of the SSPs.…”
Section: Introductionmentioning
confidence: 99%
“…of our cluster galaxies to those in the field sample of Guzmán et al (2003), employing the same SPS model in both cases will eliminate a potential source of systematic error (cf. Chen et al 2010). We therefore adopt the BC03-derived stellar masses in our subsequent analysis for consistency with previous studies.…”
Section: Comparison Of Stellar Mass Measurementsmentioning
confidence: 99%
“…This is an interesting re- sult, since BC03 models are generally used only to describe more advanced evolutionary phases of galaxy evolution (e.g. Leitherer et al 1999, Bruzual & Charlot 2003, Chen et al 2010).…”
Section: The Influence Of Different Synthetic Stellar Spectramentioning
confidence: 99%